Risk Identification of Online Learning - Riyan Maulana; Emil Biyansyahna; Siti Afriani (CV Naskah Aceh, 2024)
Riyan Maulana 1*, Emil Biyansyahna 2, Siti Afriani (3) 1 Alwashliyah University Banda Aceh 2 Syiah Kuala University 3 STIK Pante Kulu Banda Aceh *Corresponding author: riyanmaulana@unadabna.ac.id Abstract The COVID-19 pandemic has forced the education sector to shift to online learning due to social distancing, utilizing information and communication technology for teaching and learning. However, this transition presents risks such as inequality of technology access, decreased student engagement, and psychosocial impacts. This study aims to identify the risks of online learning through systematic literature review (SLR) to support effective risk management and inform education policy in the digital era. The research used the SLR method, with searches on scientific databases such as Google Scholar, Scopus, and ScienceDirect. Inclusion criteria included English and Indonesian journals (2017-2022), using the keywords